Occurrence and Impact of Intraoperative Anastomotic Leakage in Retzius-Sparing Robot-Assisted Radical Prostatectomy - Jian-Kai Chen; Yu-Jun Chang; Chi-Bo Lin; Yueh Pan; Pai-Fu Wang (Medicina)
Background and Objectives: The limited literature on the significance and risk factors of intraoperative anastomotic leakage (IAL) following Retzius-sparing robot-assisted radical prostatectomy (Rs-RARP) highlights the need for further investigation. This study aimed to assess the incidence of IAL, identify its associated risk factors, and evaluate its clinical implications. Materials and Methods: Patients with prostate adenocarcinoma who underwent Rs-RARP performed by a single surgeon between February 2015 and August 2023 were included in this study. Positive IAL was defined as the presence of anastomotic leakage identified through a water injection test performed immediately after vesicourethral anastomosis (VUA). Postoperative urinary continence was defined as the use of no pads or only a safety pad. Patients were categorized into two groups: those with positive IAL and those without. Immediate repair was performed in cases of positive IAL, and cystography was conducted approximately 10–14 days postoperatively. Chi-square test, Fisher’s exact test, Mann–Whitney U test, as well as univariable and multivariable logistic regression analyses, were used to evaluate the risk factors associated with IAL. Additionally, we analyzed the continence rate and the time to achieve continence following surgery. Results: A total of 230 patients underwent Rs-RARP for prostate adenocarcinoma performed by a single surgeon at our center during the aforementioned period. A water injection test was performed in all patients immediately after the VUA. IAL was observed in 32 patients (14%) during the water injection test. Postoperative cystography revealed very mild contrast medium leakage in only two patients (0.9%), with no impact on clinical recovery. No major IAL cases were identified on postoperative cystography. Patients with positive IAL required a significantly longer time to achieve continence compared to those without IAL (2.13 vs. 0.46 months, p = 0.008). Univariable analysis showed that a locally advanced T stage (>T2), longer console time, and absence of nerve-sparing were significantly associated with positive IAL. In multivariable analysis, a longer console time and a locally advanced T stage remained significant predictors of IAL. Conclusions: IAL detected by the water injection test was associated with the development of postoperative urinary incontinence and delayed recovery of continence. A tumor stage greater than T2 and longer console time were significant predictors of IAL. Further prospective randomized studies with larger sample sizes are required to validate our findings.